The relationship between financial incentives for athletes and Brazilian sports results in the Pan-American games - Souza, João Victor Moretti de (2025)
The aim of this study was to examine the relation between financial subsidies for athletes and attaining better sport results. The selection of data was carried out by researching Brazilian athletes who competed in the 2019 Lima Pan-American Games. The study investigated the relationship between involvement in the Brazilian Athlete Grant Program and medal achievement at the 2019 Lima Pan-American Games, using binomial logistic regression to analyze factors such as gender, grant category, and sport type. Data on 481 Brazilian athletes, distributed across 40 different sports, were collected from official sources and analyzed using IBM SPSS Statistics to determine the odds ratio of winning a medal. The analysis reveals that receiving substantial grants may be related to the improvement in sports results. The data indicate that greater investment in athletes generates better sports results. Compared with the amounts received in these years, it is possible that an athlete whose grant is not very high but is received steadily increases their chances to obtain a medal. In addition, gender did not significantly impact the results obtained, and athletes representing individual sports modalities tended to obtain more medals.